THE POSITION OF ISLAMIC LAW IN THE INDONESIAN LEGAL SYSTEM (1900-2003) - Yudian Wahyudi (Asia-Pacific Journal on Religion and Society, 2021)
This article examines the development of Islamic law in Indonesia in a chronological way within the contexts of the Dutch colonialism up to 1942, the Japanese occupation from 1942 to 1945, and the post-independence to date. It analyzes such development from the perspectives of continuity and change theory. This analysis is focused on three main themes, namely: (1) the laws on issues in worshiping practices, human relations, and crimes; (2) the subjects of the laws as found in the figures of kyais (Islamic scholars), prominent individuals influenced by either Wahhabism or Western education, and leaders of organizations; and (3) implementation of  slamic laws on women affairs. This study revealed that a number of changes in Indonesian Islamic law over the last one hundred years in which moderate Shafiite and Sufi domination of Indonesian Islamic discourse was seriouslychallenged by the most rigorous and literalist school of Islamic law as represented by Hanbalisme.